Faktor-Faktor yang Berhubungan dengan Perilaku Pengelolaan Sampah Rumah Tangga Di Kelurahan Cilandak Barat Kecamatan Cilandak Tahun 2022 - Rizky Andriyanto; Fini Fajrini; Nur Romdhona; Noor Latifah (Peneliti.net, 2023)
MENLHK, 2021 Recorded that South Jakarta is the city with the highest waste generation with a total waste generation of 1,937.54 tons/day or the equivalent of 707,201.35 tons/year. In Cilandak District itself in 2022 the volume of organic waste processed from Cilandak District is between 300 and 700 kilograms per day (Folmer, 2022). This study aims to find out